Shift of grey seal subspecies boundaries in response to climate, culling and conservation - Fietz, Katharina; Galatius, Anders; Teilmann, Jonas; Dietz, Rune; Frie, Anne Kristine; Klimova, Anastasia; Palsbøll, Per J.; Jensen, Lasse F.; Graves, Jeff A.; Hoffman, Joseph I.; Olsen, Morten Tange (Molecular ecology, 2016)
Identifying the processes that drive changes in the abundance and distribution of natural populations is a central theme in ecology and evolution. Many species of marine mammals have experienced dramatic changes in abundance and distribution due to climatic fluctuations and anthropogenic impacts. However, thanks to conservation efforts, some of these species have shown remarkable population recovery and are now recolonizing their former ranges. Here, we use zooarchaeological, demographic and genetic data to examine processes of colonization, local extinction and recolonization of the two northern European grey seal subspecies inhabiting the Baltic Sea and North Sea. The zooarchaeological and genetic data suggest that the two subspecies diverged shortly after the formation of the Baltic Sea approximately 4200 years bp, probably through a gradual shift to different breeding habitats and phenologies. By comparing genetic data from 19th century pre‐extinction material with that from seals currently recolonizing their past range, we observed a marked spatiotemporal shift in subspecies boundaries, with increasing encroachment of North Sea seals on areas previously occupied by the Baltic Sea subspecies. Further, both demographic and genetic data indicate that the two subspecies have begun to overlap geographically and are hybridizing in a narrow contact zone. Our findings provide new insights into the processes of colonization, extinction and recolonization and have important implications for the management of grey seals across northern Europe.